High Blood Pressure Prevalence, Awareness, Control, and Associated Factors in a Low-Resource African Setting - Mbouemboue, Olivier Pancha; Ngoufack, Tsougmo Jacques Olivier (Frontiers in Cardiovascular Medicine, 2019)
Introduction: Recent and contextualized data are needed to improve hypertension management known as a major cardiovascular disease risk factor regardless of the geographical area. This study aimed at assessing the prevalence of hypertension, awareness of hypertensive status, treatment and control of hypertension as well assessing the factors associated with risk of hypertension and awareness of hypertensive status in population of Ngaoundere. Methods: This was a community based cross sectional study carried out from February to December 2016. A three-stage sampling method was used for recruitment of participants. Demographic, clinical and biological data were collected and analyzed using Statistical Package for Social Sciences version 20.0. Statistical significance was set at P-value <0.05. Results: In total, 948 participants were included in the study. The overall prevalence of hypertension was 46.94% (n = 445). Fraction of hypertensive participants who were aware of their status was 36.85% (n=164). Among them, 39 (23.78%) were getting treatment and control rate was 30.56%. Age, marital status, family history of hypertension, overweight, and high serum triglyceride level were identified as independent predicting factors of hypertension, whereas female gender, age, personal history of stroke or diabetes, family history of hypertension or heart failure, overweight and abdominal obesity were those of hypertension awareness. Conclusion: The present study revealed high prevalence, extremely low awareness, treatment and control rates of hypertension in Ngaoundere community setting